1995
DOI: 10.1007/bf00192355
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic-related hypokalaemia: the role of diuretics, potassium supplements, glucocorticoids and ?2-adrenoceptor agonists

Abstract: All 5,047 consecutive inpatients admitted to the Internal Medicine Division of a teaching hospital (Zieglerspital, Berne) between 1982 and 1985 were registered in accordance with the CHDM (Comprehensive Hospital Drug Monitoring) questionnaire of adverse drug reactions (ADRs). Of them, 2,439 were treated with at least one potassium losing diuretic. The hospital records of the patients were reviewed with particular regard to serum potassium levels, and on the basis of this evaluation, the patients were assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Clinicians should balance the opposing risks of avoiding hyperkalemia and causing hypokalemia, or vice versa. For example, potassium-sparing diuretics have been shown to prevent diuretic-induced hypokalemia but are associated with an increased risk of hyperkalemia [ 39 ]. Furthermore, combinations of drugs with an associated risk of hyperkalemia (e.g., ACE inhibitor, ARBs, potassium-sparing diuretics [ 15 17 ]) or hypokalemia (e.g., thiazides or loop diuretics [ 18 ]) may rapidly precipitate serious serum electrolyte abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians should balance the opposing risks of avoiding hyperkalemia and causing hypokalemia, or vice versa. For example, potassium-sparing diuretics have been shown to prevent diuretic-induced hypokalemia but are associated with an increased risk of hyperkalemia [ 39 ]. Furthermore, combinations of drugs with an associated risk of hyperkalemia (e.g., ACE inhibitor, ARBs, potassium-sparing diuretics [ 15 17 ]) or hypokalemia (e.g., thiazides or loop diuretics [ 18 ]) may rapidly precipitate serious serum electrolyte abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent DDI group of the present study was found between corticosteroids and diltiazem or furosemide (12.8%). Corticosteroids can induce the hypokalemic effect of loop diuretics (21). Monitoring of serum electrolytes, especially potassium levels of patients, is recommended or an alternative diuretic can be substituted in order to avoid hypokalemia and subsequent arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Amiodarone may increase the serum concentration of atorvastatin, and atorvastatin toxicities (e.g., myalgia, liver function test elevations, and rhabdomyolysis) are possible [40,41]. Lower starting and maintenance doses of atorvastatin in patients taking amiodarone must be used.…”
Section: Clinically Serious Interactionsmentioning
confidence: 99%
“…In a large study of drug monitoring in hospitals, the records of 2439 patients on potassium-wasting diuretic therapy were reviewed to identify other factors that affected serum potassium levels. Oral or parenteral prednisone therapy was a significant risk factor for the development of hypokalemia [41].…”
Section: Potential Clinically Relevant Moderate Riskmentioning
confidence: 99%